The Day of Ahmed's secret - Heide, Florence Parry; Heidi Gilliand, Judith; Lewin, Ted (England : Penguin, 1990)
Truck and monkeys, cars and camels, carts and buses...the bustling street of Cairo are exciting, but today ahmed will share his secret, which is even more exciting.
Keywords: Secret -- Fiction